TERAPI AKUPRESUR LI4–CV6 DAN DEEP BREATHING UNTUK NYERI DISMENORE REMAJA DI SMAN 1 RANCAEKEK - Ecih Winengsih; Antri Ariani; Linda Rofiasari (JOMIS (Journal of Midwifery Science), 2026)
Dysmenorrhea is one of the most common gynecological problems experienced by adolescents, which can interfere with daily activities, learning concentration, and overall quality of life. In Indonesia, the prevalence of dysmenorrhea reaches 64.25%, with a high proportion among high school students. Pharmacological therapy is often used, but long-term use carries the risk of side effects. Therefore, complementary approaches such as acupressure and relaxation techniques are promising alternatives. This study aimed to determine the effect of combining acupressure at Hegu (LI4) and Qi Hai (CV6) points with deep breathing exercises on the level of dysmenorrhea pain among adolescent girls. The study employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 58 female students from SMAN 1 Rancaekek were selected using a total sampling technique. The intervention consisted of applying acupressure at LI4 and CV6 points for 5 minutes each, combined with deep breathing exercises, performed twice daily during the first two days of menstruation. Pain intensity was measured using the Numeric Rating Scale (NRS), and data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant reduction in pain (p < 0.001). Before the intervention, most respondents experienced moderate pain (69%), whereas after the intervention, the majority reported mild pain (62.1%) and some experienced no pain (29.3%). This study recommends integrating acupressure and deep breathing into school-based reproductive health programs as a safe, simple, and effective complementary therapy for managing dysmenorrhea among adolescents